Current research on prospective secondary mathematics teachers’ professional identity - Losano, Ana Leticia (2017)
Fil: Losano, Ana Leticia. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.